Applications of Proteomics and Genomics for Improving Meat Quality - Ujjan, Javed; Khushbakht, Maria; Soomroa, Tanveer; Linsen, Zan (Asian Journal of Biological and Life Sciences, 2015)
This paper introduces a series of phenotypic analyses done in parallel with genotypic analyses for the bovine meat quality. This has allowed new knowledge to be gained of the genetic, environment and management factors that impact on the carcase and eating quality, visual appeal, odour and health attributes of meat quality. The Review described involved close collaboration with commercial partners across the supply chain in the sire breeding as well as the meat processing industries. This approach has enabled timely delivery and adoption of Review results to industry in an unprecedented. A special attention will be given to meat production, as well as quality control. In the latter, a way and provides a good model for future Review. Sufficient diversity in performance and adaptability can be exploited for actual improvement accruing to conservation and development of indigenous cattle resources.
Keywords: Genomics; Markers; Meat quality; Proteomics